Combination of CRITIC Weighting Method and Multi-Atributive Ideal-Real Comparative Analysis in Staff Admissions - Waqas Arshad, Muhammad; Mesran; Setiawansyah, Setiawansyah; Suryono, Ryan Randy; Rahmanto, Yuri (Explorer, 2024)
Staff recruitment is a critical process in human resource management where organizations select and place individuals who fit the needs and goals of the company. This process involves identifying position needs, job postings, screening applicants, interviewing, skills evaluation, and making a final decision to determine the most suitable employee. The integration of CRITIC and MAIRCA allows the staff selection process to be more objective and systematic. CRITIC helps in assessing the importance of each criterion by considering its relevance, thus ensuring that the evaluation is not based on just one dimension. On the other hand, MAIRCA provides a comprehensive framework by comparing each candidate against the desired ideal standards and their actual achievements in relevant attributes. The combination of these two methods not only strengthens accuracy in staff selection, but also ensures that decisions are made in accordance with the organization's strategic goals to achieve optimal performance and effectiveness. The ranking results obtained the results of rank 1 with a value of 0.0824 obtained by Alternative G, rank 2 with a value of 0.0798 obtained by Alternative B, and rank 3 with a value of 0.0778 obtained by Alternative C.